Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1084/jem.20201631
|View full text |Cite
|
Sign up to set email alerts
|

A TLR7 antagonist restricts interferon-dependent and -independent immunopathology in a mouse model of severe influenza

Abstract: Cytokine-mediated immune-cell recruitment and inflammation contribute to protection in respiratory virus infection. However, uncontrolled inflammation and the “cytokine storm” are hallmarks of immunopathology in severe infection. Cytokine storm is a broad term for a phenomenon with diverse characteristics and drivers, depending on host genetics, age, and other factors. Taking advantage of the differential use of virus-sensing systems by different cell types, we test the hypothesis that specifically blocking TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 95 publications
0
24
0
Order By: Relevance
“…Increasing evidence indicates that excessive immune response leads to immune-mediated damage and affects disease process and prognosis ( Guo et al, 2021 ; Karki et al, 2021 ; Rappe et al, 2021 ). This emphasizes the importance of host factors in predicting clinical progression and prognosis in patients with viral infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence indicates that excessive immune response leads to immune-mediated damage and affects disease process and prognosis ( Guo et al, 2021 ; Karki et al, 2021 ; Rappe et al, 2021 ). This emphasizes the importance of host factors in predicting clinical progression and prognosis in patients with viral infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between hosts and the virus determines prognosis of the disease ( Ito et al, 2011 ; Mahler et al, 2021 ). Although an effective immune response is indispensible for eliminating virus, exaggerated response characterized by the so-called “cytokine storm” can trigger severe immune pathological damage ( Karki et al, 2021 ; Rappe et al, 2021 ). Changes in the expression levels of host factors and abnormal immunity, such as cytokine storm ( Liu et al, 2016 ; Guo and Thomas, 2017 ), lymphopenia ( Cheng et al, 2019 ; Zhang et al, 2020b ), and T cell exhaustion ( Valero-Pacheco et al, 2013 ; Diao et al, 2020 ), during virus infection have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…TLR7 agonist treatment is also not well suited for treatment of acute, severe respiratory viral lung disease with potential contribution to acute virus-induced immunopathology exemplified by a study that reported blockade of TLR7 reduced mortality in a mouse model of severe influenza. Rather than reducing the innate immune response in AECs, the TLR7 antagonist reduced excessive type I IFN and inflammatory cytokine/chemokine production by pDC and monocytes and this reduced mortality [101]. This also highlights the safety concerns related to bystander immune cell activation by topical (e.g.…”
Section: Therapeutic Targeting Of Tlr3mentioning
confidence: 96%
“…Genetic studies revealed that inborn deficiency in TLR3 and TLR7 signaling underlies defective type I IFN production and severe disease in a group of COVID-19 patients 25 , 26 . TLR7-mediated type I IFN responses in plasmacytoid dendritic cells reportedly play a critical role in protection against severe COVID-19 [27] , while uncontrolled TLR7 activation can lead to CSS in severe influenza [28] . cGAS activation following mitochondrial DNA release during SARS-CoV-2 infection was shown to elicit aberrant IFN production, which causes IFN-mediated immunopathology in severe COVID-19 [29] .…”
Section: Innate Immune Sensing Of Sars-cov-2 and Iavmentioning
confidence: 99%